The Rise of Fiscal Capacity: Administration and State Consolidation in the Holy Roman Empire - Cantoni, Davide; Mohr, Cathrin; Weigand, Matthias (Econometrica, 2024)
This paper studies the role of fiscal capacity in European state consolidation. Our analysis is organized around novel data on the territories and cities of the Holy Roman Empire in the early modern period. Territories implementing an early fiscal reform were more likely to survive, increased in size, and achieved a more compact extent. We provide evidence for the causal interpretation of these results and show key mechanisms: revenues, military investments, and marriage success. The imposition of Imperial taxes, quasi‐random in timing and size, increased the benefits of an efficient tax administration on the side of rulers, driving the implementation of fiscal centralization. Within territories, Chambers became the dominant administrative institution, tilting the consolidating states toward absolutism.